General geology and microfacies analysis of Batu Ban Chuan, Dabong, Kelantan - Zakiah Ainul Kamal (2013)
The carbonate has many importance especially in the industrial use. Depend on the physical and chemical properties of the carbonate rock, the values of it can be known. These properties results of the sedimentary and diagenetic history of the rock. Microfacies studies are relevant in evaluating the depositional environment of the sediments. The purpose of this research other than producing geological map of Batu Ban Chuan are to analyse the microfacies of Batu Ban Chuan deposit based on Folk Classification and to interpret the depositional environment of Barn Ban Chuan. The list of methods used in the research are general geological mapping, laboratory analysis wich include petrography and microfacies analysis. From the description four types of microfacies is identified which are pelmicrite limestone, biomicrite limestone, micrite limestone and dolomite. As the facies is identified, the depositional of environment for Batu Ban Chuan is interpreted as low-energy level environment.